2021
DOI: 10.1111/1440-1681.13547
|View full text |Cite
|
Sign up to set email alerts
|

Klotho inhibits H2O2‐induced oxidative stress and apoptosis in periodontal ligament stem cells by regulating UCP2 expression

Abstract: Background Periodontitis, known as a human chronic in ammatory disease, has affected the life of millions of individuals. Known risk factors such as metabolic disease and oxidative stress have been reported to be closely associated with the initiation or development of periodontitis. However, the etiology of periodontitis remains unclear. Klotho, a single-pass transmembrane protein, has been widely reported to modulate cellular processes in various diseases. However, the role of Klotho in periodontitis is unkn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…In addition, pretreatment of ARPE-19 cells with recombinant Klotho protein suppressed ROS and MDA levels induced by H 2 O 2 , elevated antioxidant enzyme (SOD2, CAT, GPX) levels, mitochondrial membrane potential, and inhibited cell apoptosis. Previous reports on Klotho attenuating oxidative stress and apoptosis in cardiomyocytes [ 36 ], Periodontal ligament stem cells [ 37 ] and lens cells [ 38 ] are consistent with our results. It is suggested that Klotho has a protective effect on oxidative stress in ARPE-19 cells.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, pretreatment of ARPE-19 cells with recombinant Klotho protein suppressed ROS and MDA levels induced by H 2 O 2 , elevated antioxidant enzyme (SOD2, CAT, GPX) levels, mitochondrial membrane potential, and inhibited cell apoptosis. Previous reports on Klotho attenuating oxidative stress and apoptosis in cardiomyocytes [ 36 ], Periodontal ligament stem cells [ 37 ] and lens cells [ 38 ] are consistent with our results. It is suggested that Klotho has a protective effect on oxidative stress in ARPE-19 cells.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that under a simulated oxidative stress circumstance by H 2 O 2 , the level of reactive oxygen species (ROS) and malondialdehyde were both reduced, meanwhile, the activity of antioxidant enzymes (including superoxide dismutase, glutathione peroxidase, and catalase) was restored, by the treatment of klotho protein in hPLSC. Moreover, the expressions of apoptotic-related proteins (including BAX and Caspase-3) in hPLSCs were also reduced by the addiction of klotho (32,40). Thus, a deficiency of klotho may attribute to the accumulation of ROS and the acceleration of cell apoptosis, leading to the deterioration of oral health eventually.…”
Section: Discussionmentioning
confidence: 99%
“…The observed association between klotho and oral health in our study was consistent with previous studies. A cross-sectional study conducted in China showed that compared with those in the healthy counterparts, the levels of klotho in the gingival crevicular fluid and gingival tissues of chronic periodontitis patients were significantly lower ( 32 ). Another cross-sectional study conducted in the US demonstrated that increased tooth pulp density was observed in a hyperphosphatemic familial tumoral calcinosis patient caused by mutations in klotho ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations